Systematic Literature Review (SLR): Technology Implementation and Digitalization in Tourism and Hotel Services - Rizky Hariyanto; Yudha Endra Pratama (Riviera Publishing, 2026)
The rapid adoption of digital technologies has fundamentally reshaped service delivery across the global tourism and hospitality sector. While an expanding body of literature addresses individual aspects of this transformation, the field still lacks a comprehensive synthesis that simultaneously maps dominant technology categories, examines prevailing methodological orientations, and critically analyzes implementation challenges across diverse tourism contexts, particularly in developing economies. This study addressed that gap through a Systematic Literature Review (SLR) of 63 peer-reviewed documents retrieved from the Scopus database (2015–2025). Documents were screened using the PRISMA protocol with explicit inclusion and exclusion criteria covering publication period, language, document type, thematic relevance, and methodological quality. Bibliometric analysis was conducted using VOSviewer (version 1.6.20) and the RStudio Bibliometrix package. Three research questions guided the synthesis: (RQ1) which technology categories dominate the literature; (RQ2) what methodological approaches characterize this field; and (RQ3) what challenges and best-practice solutions are associated with technology adoption. The findings reveal four dominant themes: (1) artificial intelligence, IoT, and smart technologies as drivers of operational efficiency and personalized service; (2) mobile applications and online platforms reshaping booking behavior within a Technology Acceptance Model (TAM) framework; (3) persistent barriers, including digital literacy gaps, data privacy concerns, and employee resistance, which are especially pronounced in SME-dominated and developing-country contexts; and (4) COVID-19 as a structural accelerant of contactless and automated service delivery. The study’s novelty lies in its cross-cutting synthesis, integrating technology classification, methodological critique, and challenge analysis while foregrounding the underexplored context of developing tourism economies. Theoretically, this review advances digital tourism literature by identifying boundary conditions of TAM and proposing an integrated analytical framework for future research. Practically, the findings provide actionable guidance for tourism managers, destination management organizations, and policymakers navigating digital transformation.